Review and Evaluation of Data Availability and Network Consistency in Wireless Sensor Networks - Tabassum, M.; Perumal, S.; Ab Halim, A.H. (Universiti Sains Islam Malaysia, 2024)
Rapid development of Information and Communication Technologies (ICTs) has greatly influenced and transformed industries. The convergence of digital media and knowledge base platforms promoted new evolving concepts and ideas between various industries to solve the complex problems. Smart grid, smart homes, smart intelligence and surveillance systems offer a wide range of connectivity and productivity to the mankind. Mainly, these systems are examples of the Internet of things (IoT) in which many sensor nodes work together to perform continuous intelligence, monitoring and management related tasks. Wireless Sensor Networks (WSN) are one of the examples of IoT networks and are being used in many industries for mobility, scalability, reliability, intelligent monitoring and management purposes. In many developed countries, WSN technology has been used to monitor the agriculture crops health and growth to boost their economy. Utilization of modern equipment in the agriculture industry is essentially required to boost people's income and create a positive impact on their social life. In this research paper, we have reviewed various WSN industrial hardware infrastructures and performe